Unraveling the pathogenicity role of the novel compound heterozygous mutations of MED25 gene in a Chinese patient with BVSYS - Zou, Linbing; Qiu, Ruikang; Dai, Zhijun; Li, Yulei; Liao, Yunjiao; Zhou, Yan (Frontiers in Genetics, 2025)
IntroductionMediator of RNA polymerase II transcription subunit 25 (MED25), a crucial component of the transcriptional coactivator complex, plays a significant role in the transcription of most RNA polymerase II-dependent genes. Mutations in MED25 have been linked to various genetic syndromes, including Basel-Vanagaite-Smirin-Yosef Syndrome (BVSYS) and Intellectual Disability (ID). This study elucidated the molecular mechanism through which compound heterozygous mutations in the MED25 gene impaired pre-mRNA splicing, ultimately causing BVSYS.MethodsWhole exome sequencing (WES) was performed to identify genetic variants, followed by Sanger sequencing for validation. Clinical data were correlated with established MED25-related syndrome phenotypes. Bioinformatics tools were utilized to predict splicing effects and protein structural alterations. Functional characterization involved in vitro minigene splicing assays for the c.1965+1dup mutation and RT-PCR analysis of patient-derived transcripts, while the impact of p.R224G was assessed through protein structure modeling.ResultsThe proband presented with clinical manifestations such as cognitive impairment, language difficulties, intellectual disability, and microcephaly. The study identified a compound heterozygous mutation in the MED25 gene (NM_030973.4), consisting of c.670C>G (p.R224G) and c.1965+1dup, which was associated with the observed clinical phenotype. Bioinformatics analysis and in vivo/in vitro splicing assays demonstrated that the c.1965+1dup mutation disrupts MED25 pre-mRNA splicing, whereas the c.670C>G (p.R224G) variant does not exhibit this effect. However, bioinformatics analysis suggested that the mutation c.670C>G (p.R224G) may affect gene function by altering the structure of the MED25 protein.ConculsionThese findings demonstrated that two mutation sites identified in the MED25 gene in this case are pathogenic or likely pathogenic and may be associated with the clinical phenotype of the proband in this study.